2020
DOI: 10.3390/ijerph17113862
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationships between Parental Migration, Home Environment, and Early Child Development in Rural China: A Cross-Sectional Study

Abstract: A growing body of literature is providing evidence of a negative association between parental migration and child development. Meanwhile, the chain of relationships between parental migration, home environment, and early child development has not yet been well documented in China. This paper investigates the interrelationships between parental migration, home environment, and early child development in an undeveloped area of western rural China. In total, 444 households were included in the study. Bayley Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
3
5
0
1
Order By: Relevance
“…However, upon conducting an analysis of each aspect of development based on sex, it was discovered that in early childhood, children raised by skipped-generation families exhibited a notable suspected delay in language development compared to children raised in non-skipped-generation families. This finding corresponds to the research conducted by Zhong J et al, which revealed a correlation between parental migration and delayed language development in children during early childhood 20 . Stimulating activities are crucial for fostering the progress of language development aspects.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, upon conducting an analysis of each aspect of development based on sex, it was discovered that in early childhood, children raised by skipped-generation families exhibited a notable suspected delay in language development compared to children raised in non-skipped-generation families. This finding corresponds to the research conducted by Zhong J et al, which revealed a correlation between parental migration and delayed language development in children during early childhood 20 . Stimulating activities are crucial for fostering the progress of language development aspects.…”
Section: Discussionsupporting
confidence: 92%
“…However, an additional study, which was also conducted in a rural region of China, yielded slightly divergent findings regarding early childhood development. Parental migration did not correlate with a child's cognitive, motor, or social-emotional development; however, it was associated with delayed language development in early childhood 20 . Recently, a prospective cohort study was conducted on Chinese children to evaluate the correlation between parental migration and various indicators of early childhood development.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…The findings also revealed that different components of family care play heterogeneous roles between parenting information and development outcomes. On the one hand, play materials are important material inputs for child development [ 11 , 12 , 32 , 33 ]. The caregiver who has received more parenting information would prepare more varieties of play materials in the household, which in turn, foster the child’s development in all four ECD outcomes.…”
Section: Discussionmentioning
confidence: 99%